ANALYSIS OF TRAFFIC FLOW PERFORMANCE COMPARISON METHOD USING MKJI, MODEL GREENSHIELDS, GREENBERG, AND UNDERWOOD AT JALAN AHMAD YANI KM.32 BANJARBARU (STA 32+450 - 32+650) - Said Lutfi Zainur Hamid; Rosehan Anwar (CERUCUK, 2017)
Traffic flow is one component that can not be separated from other components such as social activities, economic, cultural, demographic and land use patterns. Along with the growth in traffic flows is increasing rapidly, there will be traffic density. This is because the capacity density of motor vehicles on the road are huge numbers, this can cause congestion.Three models of traffic through the model approach Greenshields, Greenberg, Underwood and Indonesian Highway Capacity Manual (MKJI) 1997 provides guidelines to obtain Level Road Service of a road section.The equation for current models Banjarmasin heading Underwood Banjarbaru the model with the equation y = 63,588e-0,012x and the R value of 0.611 with a maximum volume of 2412.81 smp / hour, while for the current Banjarbaru heading to Banjarmasin obtained with the Model Greenberg equation, y = -13,75ln (x) + 88.767 and the R value of 0.476, obtained when the maximum volume amounted to 3218.98 smp / hour. Based on the predictions made, showed that in the 4th and the 5th level of service on the road Ahmad Yani KM.32 Banjarbaru is the category of class E and F. Thus it is necessary for handling that service levels can be increased and become more good. Keywords: Greenshields, Greenberg, Underwood, MKJI, Prediction.